2020
DOI: 10.1039/c9ra09576d
|View full text |Cite
|
Sign up to set email alerts
|

A slight bluish-white fluorescence from E,E-2,6-bis(4-cyanostyryl)pyridine pristine crystals

Abstract: E,E-2,6-Bis(4-cyanostyryl)pyridine pristine crystals showed slightly bluish white emission: these were mixtures of two crystals emitting blue and yellow-green regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The presence of a substituent can alter the distribution of electrons within a molecule, leading to changes in the electronic properties. It is well known that one is the inductive effect, which is based on the electronegativity of the substituent ( Mochizuki and Kusama, 2020 ). An electron-withdrawing group, such as the-CN, tends to withdraw electron density from the rest of the molecule, specifically creating a partial positive charge on the adjacent carbon atom.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a substituent can alter the distribution of electrons within a molecule, leading to changes in the electronic properties. It is well known that one is the inductive effect, which is based on the electronegativity of the substituent ( Mochizuki and Kusama, 2020 ). An electron-withdrawing group, such as the-CN, tends to withdraw electron density from the rest of the molecule, specifically creating a partial positive charge on the adjacent carbon atom.…”
Section: Introductionmentioning
confidence: 99%
“…The development of several π-conjugated oligomers has contributed to the advancement of organic optical and electronic devices. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] For example, bis-styrylbenzene derivatives (BSDs) and thiophene/phenylene co-oligomers (TPCOs) show remarkable optical and electrical characteristics. Various studies have reported the excellent photophysical properties of BSDs and TPCOs, where 1,4-bis(4trifluoromethylstyryl)benzene and α,ω-bis(biphenylyl) terthiophene (BP3T) show very low amplified spontaneous emission thresholds.…”
Section: Introductionmentioning
confidence: 99%